Synaptic Pathology in Borna Disease Virus Persistent Infection - Gonzalez-Dunia, Daniel (American Society for Microbiology, 2000)
Borna disease virus (BDV) infection of newborn rats leads to a persistent infection of the brain, which is associated with behavioral and neuroanatonomical abnormalities. These disorders occur in the absence of lymphoid cell infiltrates, and BDV-induced cell damage is restricted to defined brain areas. To investigate if damage to synaptic structures anteceded neuronal loss in BDV neonatally infected rats, we analyzed at different times postinfection the expression levels of growth-associated protein 43 and synaptophysin, two molecules involved in neuroplasticity processes. We found that BDV induced a progressive and marked decrease in the expression of these synaptic markers, which was followed by a significant loss of cortical neurons. Our findings suggest that BDV persistent infection interferes with neuroplasticity processes in specific cell populations. This, in turn, could affect the proper supply of growth factors and other molecules required for survival of selective neuronal populations within the cortex and limbic system structures.